IMPLEMENTASI KEBIJAKAN PENANGGULANGAN PANDEMI COVID-19 TAHUN 2021 DI KELURAHAN WUNGU KECAMATAN WUNGU KABUPATEN MADIUN, PROVINSI JAWA TIMUR - Eko Roedianto; Joko Pramono; Adi Purwanto (Master of Public Administration, Universitas Slamet Riyadi, 2022)
The Covid-19 pandemic is a problem that highlights the attention of many peoplein various parts of the world. Since it was first noticed from patients infected withCovid-19 in Wuhan, Hubei Province, China on December 8, 2019, the virus hasnow spread to 216 countries. This pandemic has not only threatened humanhealth, but has also affected the world economic downturn. The most affectedsectors are aviation, transportation, hotels and restaurants. This uncertainsituation will further aggravate global financial stability. The Village Governmentis at the forefront of tackling this pandemic. This research uses descriptivequalitative research methods. In accordance with the formulation of the problemand the purpose of this research, the focus in tackling Covid-19 and to measurethe success of a policy implementation according to Edward III theory can bemeasured through four dimensions, namely: Communication, Resources,Disposition and Bureaucratic Structure.Keywords: Implementation, Countermeasures, Pandemic Covid-19